AMPLIFY: a randomized, Phase III study evaluating the efficacy and safety of aclidinium/formoterol vs monocomponents and tiotropium in patients with moderate-to-very severe symptomatic COPD - Sethi, Sanjay (Int J Chron Obstruct Pulmon Dis, 2019)
BACKGROUND: AMPLIFY assessed the efficacy and safety of aclidinium bromide/formoterol fumarate (AB/FF) vs its monocomponents and tiotropium (TIO) in patients with moderate-to-very severe symptomatic COPD (NCT02796677). METHODS: In this 24-week, Phase III, double-dummy, active-controlled study, symptomatic patients (COPD Assessment Test score ≥10) were randomized to twice-daily AB/FF 400/12 µg, AB 400 µg, or FF 12 µg, or once-daily TIO 18 µg. Co-primary endpoints were change from baseline at week 24 in 1-hour morning post-dose FEV(1) (AB/FF vs AB) and in pre-dose (trough) FEV(1) (AB/FF vs FF). Non-inferiority of AB vs TIO in pre-dose FEV(1) was also an objective. Normalized area under the curve (AUC)(0–3/3 h) FEV(1) and nighttime and early morning symptoms were also assessed. A subgroup participated in a 24-hour serial spirometry sub-study. RESULTS: A total of 1,594 patients were randomized; 566 entered the sub-study. At week 24, 1-hour post-dose FEV(1) significantly improved with AB/FF vs AB, FF, and TIO (84, 84, and 92 mL; all P<0.0001). AB/FF significantly improved trough FEV(1) vs FF (55 mL, P<0.001) and AB was non-inferior to TIO. AB/FF significantly improved AUC(0–3/3 h) FEV(1) vs all comparators (P<0.0001) and provided significant improvements in early morning symptoms vs TIO. The 24-hour spirometry demonstrated significantly greater improvements with AB/FF in AUC(12–24/12 h) vs all comparators, and in AUC(0–24/24 h) vs FF or TIO at week 24. CONCLUSION: In patients with moderate-to-very severe symptomatic COPD, twice-daily AB/FF significantly improved lung function vs monocomponents and TIO, and early morning symptom control vs TIO.